2019
DOI: 10.1210/js.2019-00160
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products (AGEs), Receptor for AGEs, Diabetes, and Bone: Review of the Literature

Abstract: Diabetes compromises bone cell metabolism and function, resulting in increased risk of fragility fracture. Advanced glycation end products (AGEs) interact with the receptor for AGEs (RAGE) and can make a meaningful contribution to bone cell metabolism and/or alter function. Searches in PubMed using the key words “advanced glycation end-product,” “RAGE,” “sRAGE,” “bone,” and “diabetes” were made to explain some of the clinical outcomes of diabetes in bone metabolism through the AGE–RAGE signaling pathway. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(114 citation statements)
references
References 111 publications
1
93
1
2
Order By: Relevance
“…An increase of RAGE ligand signaling is related to different pathologies characterized by reduced bone mass/strength, including diabetes, cancer, cardiovascular disease, and neurodegeneration [32]. Although RAGE expression is upregulated in inflammatory pathological conditions, it has been suggested that RAGE signaling may have also a role in inflammation resolution and tissue repair [33]. The harmful effects of the RAGE ligands AGEs on osteoblast viability and activity have been identified [11].…”
Section: Ragementioning
confidence: 99%
“…An increase of RAGE ligand signaling is related to different pathologies characterized by reduced bone mass/strength, including diabetes, cancer, cardiovascular disease, and neurodegeneration [32]. Although RAGE expression is upregulated in inflammatory pathological conditions, it has been suggested that RAGE signaling may have also a role in inflammation resolution and tissue repair [33]. The harmful effects of the RAGE ligands AGEs on osteoblast viability and activity have been identified [11].…”
Section: Ragementioning
confidence: 99%
“…Diabetic complications and osteoporotic fracture are chronic diseases that share several features including genetic susceptibility and environmental factors [11]. In addition, both glycemic and bone homeostasis are known to be under the influence of common regulatory factors such as insulin, peroxisome proliferator-activated receptor-gamma, gastrointestinal hormones, and osteocalcin [11][12][13]. Advanced glycation end products (AGE) accumulate in diabetic dysfunction and bone homeostasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both glycemic and bone homeostasis are known to be under the influence of common regulatory factors such as insulin, peroxisome proliferator-activated receptor-gamma, gastrointestinal hormones, and osteocalcin [11][12][13]. Advanced glycation end products (AGE) accumulate in diabetic dysfunction and bone homeostasis [12]. Accordingly, the association between diabetes mellitus and bone health has long been a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of RAGE induces an inflammatory cascade that starts with activation of a transcription factor nuclear factor-kappa B (NF-κB) that promotes the expression of proinflammatory cytokines, growth factor, and adhesive molecules [12,13]. Specifically, the engagement of RAGE increases oxidative stress by activating NADPH oxidase that also increases in NF-κB stimulation [14].…”
Section: Introductionmentioning
confidence: 99%